Assembly of the exosporium layer in Clostridioides difficile spores. (June 2022) - Paredes-Sabja, Daniel; Cid-Rojas, Francisca; Pizarro-Guajardo, Marjorie
Abstract : Clostridioides difficile is a Gram-positive, spore-forming obligate anaerobe and a major threat to the healthcare system world-wide. Because of its strict anaerobic requirements, the infectious and transmissible morphotype is the dormant spore. During infection, C. difficile produces spores that can persist in the host and are responsible for disease recurrence and transmission, especially between hospitalized patients. Although the C. difficile spore surface mediates critical interactions with host surfaces, this outermost layer, known as the exosporium, is poorly conserved when compared to members of the Bacillus genus. Notably, the exosporium has been shown to be important for the persistence of C. difficile in the host. In this review, the ultrastructural properties, composition, and morphogenesis of the exosporium will be discussed.